Characteristics of green public procurement in Hungary - Boros, Anita; Kovács, László (Studia Mundi – Economica, 2022)
Green, sustainable and circular public procurement are concepts that require a completely different approach from the point of view of public procurement as well. An economic approach that goes beyond the economic aspects of occasional procurement needs and is also suitable for achieving wider effects. The legal foundations for these have already been mostly created by the legislator at the EU and national level. However, the application of narrowly or broadly interpreted green aspects requires the conscious behavior of the entire value chain of the given procurement.In our study, we examined (i) what exactly is covered by some definitions of public procurement classified under the general term of green public procurement (sustainable public procurement, circular public procurement), (ii) what is the ratio of green public procurement in Hungary, and (iii) we tried to formulate proposals for the more effective application of green public procurement.